Risk Management Method In It Project: A Review - Faahakhododo, Ikhtiar; Rianto, Indra Dwi (Bina Nusantara University, 2016)
In the development of a software, there are several aspects that must be taken to ensure that the process can produce a useful product and make a profit. This article clarified some of the methods of risk management exist. There was two techniques to determine the risks used in this study, those were Metrics of Process Structure and Referential Model or could be referred as the Comparison to the Referential Model technique. That technique will produce Software Process Meta Model, Model of Risk Management, and Manage Risks in Project models. Those models were used to help managers in mapping the risks of the project.